2016
DOI: 10.1371/journal.pone.0156334
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Intestinal Epithelial Cell Turnover by Commensal Bacteria: Role of Short-Chain Fatty Acids

Abstract: The life span of intestinal epithelial cells (IECs) is short (3–5 days), and its regulation is thought to be important for homeostasis of the intestinal epithelium. We have now investigated the role of commensal bacteria in regulation of IEC turnover in the small intestine. The proliferative activity of IECs in intestinal crypts as well as the migration of these cells along the crypt-villus axis were markedly attenuated both in germ-free mice and in specific pathogen–free (SPF) mice treated with a mixture of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
161
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(191 citation statements)
references
References 44 publications
13
161
4
1
Order By: Relevance
“…Although previous studies have demonstrated that “natural” IELs do not require commensal bacteria to populate the intestinal epithelium (Bandeira et al, 1990), we observed that γδ IEL distribution along the small intestine, positioning in the villi, motility above the basement membrane and villus-crypt bidirectional displacement are largely dependent on stimulation by the microbiota and enteric pathogens. It is possible that IELs physiologically sense EC proliferation, since our estimated IEL vertical downward displacement nearly offsets the EC growth rate described in SPF mice (approximately 6 µm/hour) (Park et al, 2016). Likewise, this coordination seems to be directed by gut microbiota, since both γδ IEL vertical displacement and epithelial cell turnover are reduced in mice devoid of microbiota (Park et al, 2016).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Although previous studies have demonstrated that “natural” IELs do not require commensal bacteria to populate the intestinal epithelium (Bandeira et al, 1990), we observed that γδ IEL distribution along the small intestine, positioning in the villi, motility above the basement membrane and villus-crypt bidirectional displacement are largely dependent on stimulation by the microbiota and enteric pathogens. It is possible that IELs physiologically sense EC proliferation, since our estimated IEL vertical downward displacement nearly offsets the EC growth rate described in SPF mice (approximately 6 µm/hour) (Park et al, 2016). Likewise, this coordination seems to be directed by gut microbiota, since both γδ IEL vertical displacement and epithelial cell turnover are reduced in mice devoid of microbiota (Park et al, 2016).…”
Section: Discussionmentioning
confidence: 74%
“…It is possible that IELs physiologically sense EC proliferation, since our estimated IEL vertical downward displacement nearly offsets the EC growth rate described in SPF mice (approximately 6 µm/hour) (Park et al, 2016). Likewise, this coordination seems to be directed by gut microbiota, since both γδ IEL vertical displacement and epithelial cell turnover are reduced in mice devoid of microbiota (Park et al, 2016). The microbiota-dependent preferential localization of γδ IELs in the upper third of villi also corresponds to the increased microbial concentration reported in that region, which has lower concentrations of anti-microbial peptides (AMPs) produced by Paneth cells in the crypts (Hooper and Macpherson, 2010).…”
Section: Discussionmentioning
confidence: 74%
“…Few studies systematically explored the influences of antibiotics on fecal SCFAs [44], and none on the influences of cefdinir or azithromycin. A very recent report showed that the microbiota of preterm infant involves a concomitant alteration in the levels of SCFAs [45].…”
Section: Resultsmentioning
confidence: 99%
“…The rate of epithelial turnover is at least partially dependent on gut bacteria since bacterial-produced short chain fatty acids promote epithelial turnover. 64 However, responses to microbial metabolites can be very cell type specific. When intestinal stem cells, a tissue compartment that is normally isolated from short chain fatty acids, encounter butyrate, their proliferation is slowed which delays tissue repair and turnover.…”
Section: Interactions Between a Host And Its Gut Bacteriamentioning
confidence: 99%